A rejuvenated approach to urban development and inequality: Young people's perceptions and experiences in Rio de Janeiro. (August 2015) - Bos, Florine; Jaffe, Rivke
Abstract: Studies of urban development, and specifically studies of urban inequality, have tended to neglect the role of young people. While development studies more broadly have begun to take young people's experiences, perceptions and practices into account, research on urban development and inequality has remained largely focused on adults. This lack of attention to young people is all the more surprising given the large percentage of urban residents in low-income countries that is under 25. Drawing on research in Rio de Janeiro's Zona Sul, this article argues for including young people in debates on urban development and urban inequality. It argues that a relational approach, juxtaposing the views and experiences of both rich and poor youth, is especially valuable in this regard, as those studies that have paid attention to youth, development and inequality tend to focus on low-income youth living in informal settlements. Based on mixed-method research with adolescents and youth (age 14–24) from both low-income and high-income areas, the article analyses young people's socio-spatial perceptions and practices. The research highlights that both groups experience urban inequality and insecurity as major and interrelated development problems, and that these issues affect their opportunities and quality of life, albeit in different ways. Highlights: Until recently, urban development studies have neglected the role of young people. Research often focuses on low-income residents in informal settlements. This paper studies the perspectives of low-income and high-income urban youth. Urban youth experience inequality and insecurity as major urban development issues.